Strategy to Increase Digital Banking Adoption at Bank Central Asia (BCA) Regional Office 2 Semarang - Denny Dwi Wiratama; Endi Sarwoko; E. Elia Ardyan (Journal Research of Social Science, Economics, and Management, 2026)
This study examines why customers of Bank Central Asia (BCA) Regional Office 2 Semarang decide to use digital banking services. The research framework is adapted from the Technology Acceptance Model (TAM) and is extended by including digital literacy, trust in transaction security, perceived usefulness, ease of use, and digital product innovation. Data were collected through a quantitative survey of 92 BCA customers and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to identify which factors are most relevant to digital banking adoption. The findings reveal that trust in transaction security (?=0.316, p<0.001) and digital product innovation (?=0.365, p<0.01) have significant positive effects on digital banking adoption, explaining 84.1% of the variance in adoption behavior. In contrast, digital literacy, perceived usefulness, and ease of use were found to be statistically insignificant predictors in this context. These results suggest that for customers with high digital maturity, security and innovation factors outweigh traditional TAM constructs in driving adoption. The study offers practical input for BCA in strengthening customer confidence, improving digital features, and encouraging more consistent use of digital banking services.